Construction of Multi-Channel Radio Frequency Plasma Jet System in Atmospheric Pressure and the Diagnosis of Plasma Parameters and I-V Characteristics - Yaseen, Waleed Ibrahim; Abd, Aseel Kamel (Iraqi Journal of Science, 2024)
In order to produce cold plasma at atmospheric pressure, a multi-channel RF, of (1, 2, 3, and 4 MHz) frequencies, plasma jet system is developed using argon as the working gas. This system consists of two parts, a multi-channel power supply (of a power of 100 W) and a plasma jet. A strong electric field is created that ionizes and excites argon ions. The I-V characteristics of the system and the electron temperature and density for different powers (20, 50, 70, and 80 W), gas flow rates (10, 20, 30, and 40 sccm) (standard centimeter cubic per minute) at different frequencies (1, 2, 3, and 4 MHz) are studied, using the optical emission spectroscopy method. This system can be used in medical applications and material treatment with high efficiency.